Improving Student Learning Motivation Through Differentiated Learning in Pancasila and Citizenship Subjects in Grade 1 of Elementary School - Sari, Pemi Purnama; Susanti, Ely; Avida, Avida; Yonanda, Pramestry; Triana, Novi (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2024)
The purpose of this study was to determine the increase in learning motivation of first grade students through differentiated learning in the subject of Pancasila and Citizenship Education. The research method used was classroom action research (CAR) with the Kemmis MC Taggart research model consisting of 2 cycles, which included four stages, namely planning, implementation, observation, and reflection. The subjects of this study were first grade students at SD Negeri 130 Palembang. The object of research in this study was students' learning motivation for the subject of Pancasila and Citizenship Education. Data collection techniques used observation sheets and interviews. The data obtained in this study were analyzed descriptively quantitatively and descriptively qualitatively. The results of cycle I showed that 40.6% of students already had learning motivation in the good and very good categories so that action was needed in cycle II because it had not reached 50% of motivated students. In cycle II, 81.2% of students already had learning motivation in the good and very good categories. Based on the results of cycles I and II, it can be concluded that there was an increase in student learning motivation through differentiated learning.